2011
DOI: 10.14341/2072-0351-5642
|View full text |Cite
|
Sign up to set email alerts
|

Lypohypertrophy in patients receiving insulin therapy: state of the art

Abstract: As known insulin therapy is associated with induration of subcutaneous fat at injections sites called lypohypertrophy. It develops at any age and at anysite regardless of duration of the treatment. The size of lypohypertrophy varies in a wide range. Numerous studies have been conducted to elucidatemechanisms of lypohypertrophy (LH) and its risk factors including young age, low or high body mass index, frequency of the change of needles andinjection sites, female gender, and type 1 diabetes mellitus. It was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
5
0
3
Order By: Relevance
“…Furthermore, it was demonstrated that ultrasonound-detected lesions consistent with lipohypertrophy more frequently than did clinical palpation, with a subset of participants exclusively having 'subclinical lipohypertrophy,' defined as lesions found only by ultrasonography. Findings of changes on ultrasonography and not on clinical examination have also been reported in one other series in which locations of lipohypertrophy had already been established [17]. In the Volkova study [17], the presence of these lesions was noted in 66% of individuals, results similar to those of the present study in which 52.4% of participants were found to have subclinical lesions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, it was demonstrated that ultrasonound-detected lesions consistent with lipohypertrophy more frequently than did clinical palpation, with a subset of participants exclusively having 'subclinical lipohypertrophy,' defined as lesions found only by ultrasonography. Findings of changes on ultrasonography and not on clinical examination have also been reported in one other series in which locations of lipohypertrophy had already been established [17]. In the Volkova study [17], the presence of these lesions was noted in 66% of individuals, results similar to those of the present study in which 52.4% of participants were found to have subclinical lesions.…”
Section: Discussionsupporting
confidence: 90%
“…Findings of changes on ultrasonography and not on clinical examination have also been reported in one other series in which locations of lipohypertrophy had already been established [17]. In the Volkova study [17], the presence of these lesions was noted in 66% of individuals, results similar to those of the present study in which 52.4% of participants were found to have subclinical lesions. Half of the individuals with subclinical lesions (24.3%) had no other findings of lipohypertrophy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations